2000
DOI: 10.1111/j.1471-0528.2000.tb11705.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar syringoma showing progesterone receptor positivity

Abstract: Case reportA 27 year old woman was seen in our clinic for pruritus vulvae. Physical examination revealed multiple 3-5 mm sized symmetrical skin coloured papules on both labia majora (Fig. 1). The lesions had been present for three years and were pruritic. There were no similar lesions elsewhere in the body. There was no family history of similar lesions. An incisional biopsy was performed under local anaesthesia and the histopathological diagnosis was syringoma (Fig. 2).She was admitted and the lesions on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…Wallace and Smoller13 reported that eight of nine syringoma cases showed strong nuclear and cytoplasmic progesterone receptor positivity, supporting the hypothesis of hormonal influence on syringoma. Yorganci et al14 reported a vulvar syringoma showing progesterone receptor positivity. Timpanidis et al15 also reported an eruptive clear cell syringoma associated with diabetes in which immunohistochemical staining showed negativity for ER and strong positivity for PR.…”
Section: Discussionmentioning
confidence: 99%
“…Wallace and Smoller13 reported that eight of nine syringoma cases showed strong nuclear and cytoplasmic progesterone receptor positivity, supporting the hypothesis of hormonal influence on syringoma. Yorganci et al14 reported a vulvar syringoma showing progesterone receptor positivity. Timpanidis et al15 also reported an eruptive clear cell syringoma associated with diabetes in which immunohistochemical staining showed negativity for ER and strong positivity for PR.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with vulvar syringoma may complain of severe itching [46]. Increased pruritus during menstruation and detection of ER and PR in some patients suggested that hormonal factors play role in the development of vulvar syringomas [4, 7, 8]. Pruritus was frequent in the largest series reported by Huang et al; however, investigators did not detect positivity for ER and PR [5].…”
Section: Discussionmentioning
confidence: 99%
“…In a case report by Yorganci et al ., immunohistochemistry of vulvar syringoma was shown to display progesterone positivity. [5] Vulvar syringomas with vulvar prutitus has been reported in a 9 year old child. [6] Venerophobia may sometimes be associated with genital lesions.…”
Section: Discussionmentioning
confidence: 99%